À qui profitent les politiques d’aide à l’acquisition de logements à Bruxelles ? - Alice Romainville (Brussels Studies, 2010)
The ownership support policies implemented by the Brussels Region are intended for certain categories of household and target certain neighbourhoods in the centre of the first ring. Via the different measures which have been established, the Region channels private investment towards certain working-class neighbourhoods to which it would like to attract private developers and a more well-to-do population.The analysis shows that the tools intended for “middle-income” households are used mainly in the central neighbourhoods, in particular along the canal, whereas the measures intended for the most disadvantaged households cause migrations from the central areas towards the western part of the Region. Ownership support has enabled a significant improvement in the situation of many households, but until now has only been relatively successful. Locally, the population movements it causes may, however, have a considerable social impact, all the more so since part of the targeted neighbourhoods have already experienced gentrification phenomena and high rent increases.